PESAN MORAL PADA FILM IMPERFECT ANALISIS CHARLES SANDERS PEIRCE - dewintha, erfina dewintha; Angel Purwanti,S.sos.,M.I.Kom (LPPM Universitas Putera Batam, 2022)
Films can be used to send messages, for example, in the form of moral messages contained in a film. The definition of morality in the general Indonesian dictionary is good or bad of aon and a person’s behaviouriourhis shows that morality is part of the term used in conveying the determinants of good and bad human behaviour. The purpose of this study is to determine the meaning and value of the moral message contained in the imperfect film. The design in this study uses the Semiotic Analysis method from Charles Sanders Pierce by taking the constructivism paradigm to see the moral message in the film Imperfect. The results of this study explain that there are several body shaming behaviours, namely physical viewing, ridicule and ridicule and the positive side is the existence of self-respect in religious tolerance, attention, and self-confidence. The conclusion shows that body sharing shaming behaviourhavioubehaviour bullet dbulletsecure so that it is very disturbing mentally, where essence he needs to get self-esteem from respect for himself, others, as well as the environment and life